Synthesis and thermal studies of some Metal Oxides (LIA102, AI2O3, FE203) / Nur Shazlinda Muhammad Hanif - Muhammad Hanif, Nur Shazlinda (2010)
Metal Oxides compounds, L1AIO2, AI2O3, Fe203 have been synthesized. Thermogravimetry and differential scanning calorimetry (TG-DSC), and elemental analysis were used to study the thermal behavior of these compounds. The TG- DSC curves show the LiA102, AI2O3, Fe203 compounds shows several weight losses. The thermal stability of the metal oxides depends on the nature of the individual materials. These curves also show that the thermal decompositions occurs in several steps depending on the respective metal oxides.